Pertumbuhan Ekonomi Kabupaten Lima Puluh Kota: Analisis Sektor Ekonomi Unggulan dan Pengeluaran Pemerintah - Sumarni, Leli; Saputri, Olga Dwi (SAFE-Network, 2024)
This research analyzes the influence of leading economic sectors and government spending on economic growth in the Limapuluh Kota Regency. Secondary data is used to obtain information needed for research analysis. The analytical methods used are quantitative descriptive analysis and qualitative analysis. The qualitative analysis uses the Location Quotient (LQ) method and Growth Ratio Model (GRM) to identify leading sectors in the Limapuluh Kota Regency. The Ordinary Least Square (OLS) approach analyzes the influence of leading economic sectors and government spending on economic growth statistically. The results of this research found that 3 sectors were categorized as superior using the LQ method and 8 sectors were categorized as potential using the GRM method. Then a regression analysis was carried out with the results that the mining sector and government spending did not significantly affect economic growth. Meanwhile, the agricultural sector and the construction sector have a significant influence on economic growth in Limapuluh Kota Regency.